Przegląd wybranych modeli gospodarki narodowej i ich ewolucja - Bal-Domańska, Beata (The review of selected models of national economy and their evolution, 2005)
Econometric models of national economy make up a valuable and indispensable tool in economic research. Since the first national economy models have been created one may observe constant development of this field of econometrics. Not only new macro-models are being created and depict new areas of economic reality, but also the already existing ones are continuously reconstructed. The article presents general tendencies for macro-modelling development, as well as the review of different types of macro-models, including Polish economy models of W series, HERMIN type models and multinational macro-econometric multi-country models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 148-161